LAND ACQUISITION REGULATION FOR INFRASTRUCTURE DEVELOPMENT IN INDONESIA: THE PROBLEM OF EFFICIENCY OF ITS PERFORMANCE - Iwan Erar Joesoef, Muhammad Helmi Fahrozi, Wardani Rizkianti, Siti Nurul Intan Sari D, Sylvana Murni Deborah Hutabarat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this article is to investigate the problem of inefficiency of Land Acquisition performance. The scope of this research is concerning to land acquisition for public purposes like developing of infrastructures in Indonesia, especially toll road infrastructure development. The methods used in this research is qualitative by collecting data from the source, there are: journals, report, conference, seminars, scripts of thesis and dissertation concerning this topic. The result of this research, the local government set up the committee for land acquisition (P2T) both for province level or district level. In its realization, such as toll road infrastructure development, in addition to setting up such P2T, the central government through ministry of public works and people housing development (PUPR) also setting up the land acquisition team (TPT) in order to assist P2T. Of which, there are many constraints such as inefficiency and ineffectiveness in performing of land acquisition both upon the institution or the procedure, and also arising the risk of the government budget usage.